ChemInform Abstract: Advances in the Colloidal Synthesis of Two‐Dimensional Semiconductor Nanoribbons. Issue 29 (1st July 2013) - Yang, Jiwoong; Son, Jae Sung; Yu, Jung Ho; Joo, Jin; Hyeon, Taeghwan
Abstract Review: emphasis on CdSe; 84 refs.